Clinical Efficacy and Side Effects of Nabumeton Compared to Meloxicam in Osteoarthritis Pain - Ade John Nursalim; Suzanna Ndraha (The Indonesian Society for Digestive Endoscopy, 2013)
Background: Most patients who use non steroid anti-inflammatory drug (NSAID) in long-term or high-dose will experience NSAID gastropathy that appears as dyspepsia complaints. The aim of this study is to assessthe efficacy of nabumeton and incidence of dyspepsia as side effect of treatment using nabumeton compared to meloxicam in patients with pain due to osteoarthritis. Methods: Sixty patients with pain due to osteoarthritis at internal medicine clinic in Koja Hospital were included in this study and were given meloxicam or nabumeton within February 29th to March 25 in double-blind manner. Primary disease pain degree and heartburn pain degree were evaluated three days after administration of the drug and a week was added if necessary. The statistical analysis used were student t-test to compare changes in pain scores between the 2 groups, and Chi-square test to assess differences in the number of dyspepsia in both groups.Results: Pain scale reduction in meloxicam group was 0.57 ± 0.67 points, which is less than 1.27 ± 0.74 points in nabumeton group. In addition, the average recurrence of heartburn in the meloxicam was 18 out of 30 (60%) patients in total, while the average recurrence of heartburn in nabumeton was 2 out of 30 (60%) patients.Conclusion: The use of nabumeton pain medication is better in terms of efficacy and side effects of heartburn compared to meloxicam.Keywords: osteoarthritis, joint pain, meloxicam, nabumeton